INFLUENCE OF "FITOBIOSOL" MICROBIOLOGICAL DRUG ON GROWTH, YIELD AND QUALITY OF BROCCOLI (American Journal of Interdisciplinary Research and Development, 2022)
In this article, the parameters of the microbiological drug "Fitobiosol" are given with a deep scientific analysis of the results of the research carried out in order to study the effect of the microbiological drug "Fitobiosol" on the growth, yield and quality of broccoli (Brassica oleracea var.italika). Also, the effect of the drug "Fitobiosol" on the fruit composition of broccoli cabbage is recorded in the article.